INTERNATIONAL COMPETITIVE BIDDING IN THE CONTEXT OF E-COMMERCE DEVELOPMENT - V. N. Kirillov (Vestnik MGIMO-Universiteta)
Review of the textbook by A.N. Zakharov. International Competitive Bidding: studies. 3rd ed. Moscow: MGIMO - University, 2018. - 248, [1] p.